2010
DOI: 10.1177/1759720x10383076
|View full text |Cite
|
Sign up to set email alerts
|

Chondroitin sulfate in the treatment of osteoarthritis: from in vitro studies to clinical recommendations

Abstract: Chondroitin sulfate (CS) is recommended as a therapeutic intervention in the multimodal approach of osteoarthritis (OA) management. CS has been studied extensively to describe its pharmacology (pharmacokinetic, in vitro and in vivo effects) and its clinical efficacy. Various results have been reported depending on the system of evaluation (model, dosage and duration) and the source of CS (origin and quality). The purpose of this review was to gather most of the available information about CS and to discuss its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
99
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(106 citation statements)
references
References 71 publications
0
99
0
7
Order By: Relevance
“…With the exception of acetominophen, all these agents have been demonstrated to reduce the production of pro-inflammatory and catabolic mediators (cytokines, prostanoids, MMPs or ROS) by joint cells. These aspects have been well documented in some recent reviews [Henrotin et al 2010[Henrotin et al , 2011[Henrotin et al , 2012. Herein, we overview the potential anti-angiogenic properties of these compounds.…”
Section: Are the Current Treatments Of Oa Antiangiogenic?mentioning
confidence: 99%
“…With the exception of acetominophen, all these agents have been demonstrated to reduce the production of pro-inflammatory and catabolic mediators (cytokines, prostanoids, MMPs or ROS) by joint cells. These aspects have been well documented in some recent reviews [Henrotin et al 2010[Henrotin et al , 2011[Henrotin et al , 2012. Herein, we overview the potential anti-angiogenic properties of these compounds.…”
Section: Are the Current Treatments Of Oa Antiangiogenic?mentioning
confidence: 99%
“…CS-C is a compound available for the treatment of OA [21], and it attenuates inflammatory responses in murine macrophages via the suppression of NF-κB nuclear translocation [22], indicating that CS-C might be able to suppress the inflammatory responses induced by the injection of cationic lipoplexes. These results suggested that sequential injection of CS-C plus cationic lipoplexes had no side-effects with regard to hepatoxicity regardless of the injection route of CS-C.…”
Section: Gene Knockdown In Livermentioning
confidence: 98%
“…CS is an anionic linear polysaccharide, which consists of alternating disaccharide units of β-glucuronic acid-(1-3)-N-acetyl-β-galactosamine-6-sulfate (Figure 1), and it can bind to CD44. CS is currently applied as a symptomatic slow-acting drug for osteoarthritis (SYSADOA) agent in the treatment of osteoarthritis (OA) [52]. Uchida et al reported that the addition of CS to pDNA/poly(ethylene glycol) (PEG)-block-poly N-[N-(2-aminoethyl)-2-aminoethyl]aspartamide (PEG-PAsp(DET)) polyplexes markedly reduced damage of cellular membrane after in vitro and in vivo gene transfections [53].…”
Section: Polyplexes or Lipoplexes Modifi Ed With Chondroitin Sulfatementioning
confidence: 99%
“…Regarding the side effects, sequential injection of αPGA plus siRNA lipoplexes exhibited hepatic damage and resulted in the induction of in lammatory cytokines such as TNFα and interleukin-10 in serum, but sequential injection of CS plus siRNA lipoplexes did not [55]. CS is a compound with an anti-in lammatory activity and available for the treatment of OA patients [52]. CS attenuates in lammatory responses in macrophages via the suppression of NF-κB nuclear translocation [89,90].…”
Section: Sequential Injection Of Anionic Polymer and Sirna Lipoplexesmentioning
confidence: 99%